(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article presents an analysis of the literature devoted to the study of the health status of newborns who have suffered perinatal hypoxia due to severe preeclampsia in mothers. The relationship of preeclampsia with fetal growth retardation, premature delivery , pathology of the neonatal period and the delayed effect of preeclampsia on intellectual development, metabolism and the cardiovascular system are discussed. Given the role of vascular endothelial growth factor in the formation of preeclampsia and endothelial reparation, interest in its level in newborns and its role in the formation of adaptive reactions of the circulatory system in newborns is justified. There is no consensus on this issue in the literature, and the problem of reducing the degree of hypoxic damage to organs and tissues in children in the early neonatal period remains relevant in practical neonatology.